Perancangan Jaringan Hotspot Di Universitas Nahdlatul Ulama Sumatera Barat Menggunakan Mikrotik Dalam Manajemen Bandwidth - Kurniawan, Indra; Eka Putra, Dian; Eko Syaputra, Aldo (Jurnal TEFSIN ( Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Hotspot networks, better known as Wi-Fi networks, have become a necessity for companies or agencies, both government and private because of the relatively low cost to implement in the work environment. Installation of Wi-Fi network devices is more flexible because it does not require a cable connection between clients, it is enough to use an access point device as a hotspot network transmitter and MikroTik RB-941-2nD which is used as a hotspot network traffic controller. The research method uses experimental research to collect data for each necessary variable. Each user profile that will connect to the hotspot network will be asked to fill in a username and password on the login page that has been configured by the admin using the Winbox application which is an application for MikroTik configuration. In addition, the Winbox admin application can limit the bandwidth speed used by each user profile so that the hotspot network becomes stable and prevents bandwidth leakage at Nahdlatul Ulama University, West Sumatra.